A STATE INTERVENTION MODEL IN URBAN REGENERATION: DEVELOPMENT AND INTERNAL COHESION - Roberto Cervelló Royo; Ruben Garrido-Yserte; Baldomero Segura García del Río (European Regional Science Association (ERSA), 2011)
This work provides an analysis and an optimization model of the spatial impact for the externalities derived from the state interventions in terms of urban regeneration and rehabilitation of degraded and segregated historic areas. From the amount invested and state intervention locations, an impact index is put forward. The spatial distribution of these impact indexes in the interventions' area of influence will be the basis for the analysis; hence, by setting some specific objectives of the decision agent about this distribution homogeneity and with the aim of avoiding inner segregation and facilitate the development and cohesion of the neighborhood as a whole, we propose a model which will allow us to allocate the budget available among the different locations fixed a priori. By means of a comparison between the spatial distributions of impact indexes obtained in both situations, a measure of the intervention process and its impact can be obtained.
Keywords: 330